1992
DOI: 10.1002/ccd.1810270412
|View full text |Cite
|
Sign up to set email alerts
|

PTCA with side‐by‐side balloon using fixed guide wire systems: A potential alternative autoperfusion device‐an in vitro study

Abstract: The use of "hugging balloons" for the implementation of a coronary angioplasty is a well-known and much-written-about technique. It has not, on the other hand, ever been stressed that two inflated hugging balloons are not totally obstructive, leaving enough space, between the balloons and the arterial wall, for perfusion. The cross section of this free area can be as much as 12% of the total arterial cross section, when the side-by-side balloons are of a relatively similar size. Calculations show that similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the early days of coronary angioplasty, an auto perfusion balloon angioplasty catheter was used for long balloon inflation, which was based on the hypothesis that the loose flap of dissection may be definitively “tacked back” and might deliver a better result [ 22 24 ]. Another study found that approximately half of patients whose initial angioplasty failed could be treated by prolonged balloon dilation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the early days of coronary angioplasty, an auto perfusion balloon angioplasty catheter was used for long balloon inflation, which was based on the hypothesis that the loose flap of dissection may be definitively “tacked back” and might deliver a better result [ 22 24 ]. Another study found that approximately half of patients whose initial angioplasty failed could be treated by prolonged balloon dilation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the early days of coronary angioplasty, an autoperfusion balloon angioplasty catheter was used for long balloon inflation, which was based on the hypothesis that the loose flap of dissection may be definitively "tacked back" and might deliver a better result [22][23][24]. A human study found that in approximately half of patients whose initial angioplasty was a failure, could be reverted to a success by prolonged dilation [25].…”
Section: Procedural Outcomesmentioning
confidence: 99%